Community outreach workers: Perceived practices and impacts on families and young children. (30th September 2020) - Roy, M; Lavoie-Trudeau, E; Benkhalti, M; Couturier, Y; Lane, J; Clapperton, I; Roy, M A; Bibeau, L; Ouellette, M; Camden, C
Abstract: Background: Community outreach workers support individuals accessing healthcare and other services that could be useful to respond to their needs. Even though community outreach workers have been working in the province of Quebec (Canada) for the past 40 years, their practice is poorly documented and evaluated, especially with respect to young children aged 0 to 5 years. This study aimed to document the practice of community outreach workers and its perceived impacts among children and families. Methods: A qualitative methodology with a descriptive research design was used. We performed a content analysis on 55 scientific and grey literature documents, 24 individual interviews, and 3 focus groups with stakeholders including parents, community outreach workers, healthcare employees, and inter-sectoral partners. Results: Our analysis reveals three main themes: 1) characteristics of the population served, 2) concrete actions performed by community outreach workers, and 3) perceived impacts of community outreach on families and children. Community outreach workers were perceived as essential to reach families with vulnerable circumstances and children with special needs. With respect to concrete actions, community outreach workers were reported to tailor their interventions to respond in different but complementary ways to the healthcare system. Perceived impacts included increased access for children and families to appropriate services, decreased social isolation, increased empowerment (especially with respect to parental abilities), increased social capital of families, and confidence towards the healthcare system. Results showed that community outreach workers helped to reduce inequalities in health Conclusions: Community outreach work help the healthcare system to fulfill its legal mandate to protect citizen and increase health and well-being. It is crucial that such type of proximity approaches be not only encouraged but also sustained. Key messages: Community outreach workers adapt their practices to act in a complementary way to the healthcare system. Community outreach workers help to reduce inequalities in health.